Optimization of PEG-modified phenolic foam for enhanced CO2 adsorption: A micro-meso structural approach - Rezvaneh Eshraghi; Mohammad Fasihi; Ahad Ghaemi (Results in Engineering)
This study explores the chemical modification of phenolic foams (PHFs) with polyethylene glycol (PEG) to enhance their carbon dioxide (CO2) adsorption capacity. PEG was incorporated into the PHF matrix at concentrations of 2–8 wt %, enhancing the foam's micro- and mesoporous structure. Structural analysis was conducted using scanning electron microscopy (SEM), while textural properties were evaluated through Brunauer-Emmett-Teller (BET) surface area analysis, highlighting increased surface area and CO2 interaction. X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and Thermogravimetric Analysis (TGA), confirmed that PEG chemically integrated into the phenolic resin network, improving pore uniformity and surface area. The thermal degradation results indicated that PEG-modified foams maintained structural integrity at higher temperatures, suggesting suitability for high-temperature CO2 capture applications. Using response surface methodology (RSM), 4 wt % PEG was determined to be optimal, achieving a CO2 adsorption capacity of 8.43 mmol/g at 298 K and 9 bar, which is 21 % higher than that of unmodified foams. Moreover, the CO2/N2 selectivity of PEG-modified PHF was around 23 % higher than that of the PHF sample. The adsorption process was characterized by multilayer adsorption on heterogeneous surfaces, following the Freundlich model, with kinetic analysis revealing a fractional-order mechanism driven by chemisorption. Thermodynamic evaluations indicated the process is exothermic and spontaneous, with increased efficiency at lower temperatures. This research highlights the potential of PEG-modified PHFs as high-performance, scalable materials for carbon capture, offering an innovative approach to addressing CO2 emissions and global climate challenges.